Efektivitas Penggunaan Senjata Api di Direktorat Intelkam Kepolisian Daerah Sumatera Selatan - Zachri, M. Syamsul; Sandy, Amiruddin; Saswita, Yanuar (@-Publik: Jurnal Administrasi Publik, 2023)
The use of firearms by the National Police as part of the implementation of the use of force in police actions must be carried out in a manner that is not contrary to the rule of law, in line with legal obligations and continues to respect / uphold human rights, as stipulated in Article 8 of the National Police Chief Regulation Number 1 of 2009. In improving the sense of security and order while anticipating the occurrence of various problems in the field, currently police officers at the Directorate of Intelkam Polda South Sumatra for new members are taking psychological tests for the use of firearms to be used by these police officers on duty. This firearms use test is in order to improve the security and order facilities of officers in maintaining security and order in the community. there are several problems related to the use of firearms at the Directorate of Intelkam Polda South Sumatra including: 1) The tight administrative requirements in obtaining permission to use firearms at the Directorate of Intelkam Polda South Sumatra, 2) The absence of regular maintenance and rejuvenation activities for existing firearms for police officers at the Directorate of Intelkam Polda South Sumatra. Based on the identification of these problems, the formulation of the problem is how the effectiveness of the use of firearms at the Directorate of Intelkam Polda South Sumatra. The purpose of this study was to analyze the effectiveness of the use of firearms at the Directorate of Intelkam Polda South Sumatra. This research uses a qualitative approach supported by quantitative data. The conclusion that can be drawn is that the activities of using firearms at the Directorate of Intelkam Polda South Sumatra at the Directorate of Intelkam Polda South Sumatra have been running effectively, the use of firearms at the Directorate of Intelkam Polda South Sumatra can improve the performance of police officers who are working.